DAYA TERIMA COOKIES TEPUNG IKAN CAKALANG DAN TEPUNG KACANG MERAH - Niron, Maria; Saleh, Asmulyati S; Hasan, Tobianus; Bere, Dionisius A (Poltekkes Kemenkes Kupang, 2025)
Nutrition problems in Indonesia that remain a serious concern are undernutrition and malnutrition, especially Protein Energy Malnutrition (PEM). Undernutrition refers to nutritional status measured using the indicator Weight for Height (BB/TB) with a z-score between -3SD to <-2SD. Data from the World Health Organization (WHO) shows that 54% of deaths in children under five are caused by protein energy malnutrition. This study aims to determine the effect of substitution of tuna flour and red bean flour on the acceptability of cookies. This research is an experimental research with a Completely Randomized Design (CRD). Substitution of tuna and red bean flour was done in three treatments: F1 (30%:5%), F2 (20%:10%), and F3 (10%:15%). Organoleptic test was conducted by 30 panelists from students of Poltekkes Kemenkes Kupang. Data analysis used ANOVA test to determine significant differences between treatments. The results of the organoleptic test showed that cookies with a substitution of tuna flour and red bean flour in treatment F3 had the highest level of acceptance in the aspects of color, aroma, texture, and taste. The average organoleptic assessment shows the like category. ANOVA test showed significant differences between treatments in the aspects of color, aroma, texture, and taste.